Magic trees in "Children’s and Household Tales" by the Brothers Grimm. - Kotlarska, Izabela (Literatura Ludowa. Journal of Folklore and Popular Culture, 2021)
On the basis of Children’s and Household Tales by Jakub and Wilhelm Grimm, translated by Eliza Pieciul-Karmińska, a folklore analysis was carried out in search of magic trees appearing in these narratives. None of the trees presented in this collection were objects of worship, but represented specific beliefs related to its appropriate treatment or magical features. Two groups of trees can be distinguished from the collected material: mediating and miraculous. In the first group, various species of plants appeared, according to folk beliefs they connected reality with the underworld, the supersensory world, or had a connection with the devil. The souls of prematurely deceased people were enchanted in trees, but also living people were turned into them. In the second group of miracle trees there was a talking apple tree, a birch that was the home of a golden bird, a golden-silver tree that had grown from the guts of the magic helper. The analyzed examples represent specific meanings they have in a complex system of folk symbols and stereotypes.